Terpaan Media Sosial dalam Minat Fashion dan Kepercayaan Diri Remaja - Septian Mulyadi; Hana Silvana (Universitas Pendidikan Indonesia, 2021)
ABSTRACTConfidence is currently a problem that is often experienced by teenagers, especially when using social media. Even according to psychologists, social media at this time is one of the triggering factors for the crisis of self-confidence in adolescents. But on the other hand, the use of social media is a necessity to obtain sources of information, one of which is about fashion content. One of the social media that is often used by teenagers today is Twitter. Twitter is popular because of the auto base feature that can send tweets anonymously. This study was conducted to prove whether individuals who have an interest in fashion will be affected by their self-confidence by being exposed to the @ustadchen Twitter account. In assisting the research, a quantitative approach is used with the moderate regression method. The participants in this study were 383 active followers of the @ustadchen Twitter account by filling out a statement questionnaire. The results showed that interest in fashion with indicators of interest, attention, and desire had a positive and significant effect on adolescent self-confidence. In addition, media exposure with indicators of frequency, duration, and attention strengthens the influence of fashion interest on adolescent self-confidence. This shows that the higher the media exposure of the @ustadchen Twitter account, the influence of fashion interest on adolescent self-confidence increases. Based on the results of the study, interest in fashion and media exposure affects adolescent confidence in the positive and significant categories, so in this case, social media plays a role in building adolescent confidence.Keyword: fashion interests; media exposure; twitter; confidence; youthABSTRAKKepercayaan diri pada saat ini menjadi masalah yang sering dialami oleh para remaja, terlebih ketika menggunakan media sosial. Bahkan menurut psikolog, media sosial pada saat ini merupakan salah satu faktor pemicu krisis kepercayaan diri pada remaja. Namun disisi lain, penggunaan media sosial menjadi suatu kebutuhan untuk memperoleh sumber informasi, salah satunya yaitu mengenai konten fashion. Salah satu media sosial yang sering digunakan oleh remaja sekarang yaitu twitter. Twitter digemari karena adanya fitur autobase yang bisa mengirimkan cuitan secara anonim. Penelitian ini dilakukan untuk membuktikan apakah individu yang memiliki minat fashion akan terpengaruh kepercayaan dirinya dengan terpaan media akun twitter @ustadchen. Dalam membantu penelitian, digunakan pendekatan kuantitatif dengan metode regresi moderasi. Partisipan dalam penelitian ini yaitu 383 pengikut aktif akun twitter @ustadchen dengan mengisi kuisioner pernyataan. Hasil penelitian menunjukkan bahwa minat fashion dengan indikator ketertarikan, perhatian dan keinginan berpengaruh positif dan signifikan terhadap kepercayaan diri remaja. Selain itu, terpaan media dengan indikator frekuensi, durasi dan atensi memperkuat pengaruh minat fashion terhadap kepercayaan diri remaja. Hal tersebut menunjukkan bahwa semakin tinggi terpaan media akun twitter @ustadchen, maka pengaruh minat fashion terhadap kepercayaan diri remaja makin meningkat. Berdasarkan hasil penelitian tersebut, minat fashion dan terpaan media mempengaruhi kepercayaan diri remaja dalam kategori positif dan signifikan, maka dalam hal ini media sosial berperan dalam membangun kepercayaan diri remaja.Kata Kunci: minat fashion; terpaan media; twitter; kepercayaan diri; remaja